2021
DOI: 10.18865/ed.31.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health as Potential Influencers of a Collaborative Care Intervention for Patients with Hypertension

Abstract: Objectives: The use of collaborative care teams, comprising nurse care managers and community health workers, has emerged as a promising strategy to tackle hyperten­sion disparities by addressing patients’ social determinants of health. We sought to identify which social determinants of health are associated with a patient’s likelihood of engaging with collaborative care team members and with the nurse care manager’s likelihood of enlisting community health workers (CHW) to provide additional sup­port to patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…175 Previous studies demonstrated the success of efforts such as community health worker or patient navigator programs, 176 social risk score assessments, 177,178 and health behavior counseling 179 on reducing blood pressure, CVD risk, and LDL (low-density lipoprotein) levels. 180 For example, the RICH LIFE (Reducing Inequities in Care of Hypertension: Lifestyle Improvement for Everyone) 176 intervention sought to reduce hypertension control disparities through a collaborative care model that involved nurse care managers to coordinate care for patients with comorbidities, whereas the WISEWOMAN (Well-Integrated Screening and Evaluation for Women Across the Nation) 179 intervention introduced lifestyle counseling from bilingual community health workers to improve cardiovascular behaviors among Latina women. Other interventions have targeted systematic approaches to SDoH integration in clinical care, such as developing a modified version of the Framingham CVD Risk Score 177 and adding measures of SDoH to improve the predictive accuracy of CVD risk models.…”
Section: The Role Of Interventions In Addressing the Impact Of Social...mentioning
confidence: 99%
See 1 more Smart Citation
“…175 Previous studies demonstrated the success of efforts such as community health worker or patient navigator programs, 176 social risk score assessments, 177,178 and health behavior counseling 179 on reducing blood pressure, CVD risk, and LDL (low-density lipoprotein) levels. 180 For example, the RICH LIFE (Reducing Inequities in Care of Hypertension: Lifestyle Improvement for Everyone) 176 intervention sought to reduce hypertension control disparities through a collaborative care model that involved nurse care managers to coordinate care for patients with comorbidities, whereas the WISEWOMAN (Well-Integrated Screening and Evaluation for Women Across the Nation) 179 intervention introduced lifestyle counseling from bilingual community health workers to improve cardiovascular behaviors among Latina women. Other interventions have targeted systematic approaches to SDoH integration in clinical care, such as developing a modified version of the Framingham CVD Risk Score 177 and adding measures of SDoH to improve the predictive accuracy of CVD risk models.…”
Section: The Role Of Interventions In Addressing the Impact Of Social...mentioning
confidence: 99%
“…174 Additionally, the American Heart Association has suggested expanding SDoH education for cardiovascular health providers at all levels, improving tools using electronic health records to incorporate SDoH screening and referrals into clinical practice, and expanding SDoH interventions to address upstream determinants of CVD such as poverty, education, and health care coverage. 175 Previous studies demonstrated the success of efforts such as community health worker or patient navigator programs, 176 social risk score assessments, 177,178 and health behavior counseling 179 on reducing blood pressure, CVD risk, and LDL (low-density lipoprotein) levels. 180 For example, the RICH LIFE (Reducing Inequities in Care of Hypertension: Lifestyle Improvement for Everyone) 176 intervention sought to reduce hypertension control disparities through a collaborative care model that involved nurse care managers to coordinate care for patients with comorbidities, whereas the WISEWOMAN (Well-Integrated Screening and Evaluation for Women Across the Nation) 179 intervention introduced lifestyle counseling from bilingual community health workers to improve cardiovascular behaviors among Latina women.…”
Section: The Role Of Interventions In Addressing the Impact Of Social...mentioning
confidence: 99%
“…Together, we should prioritize meeting patients where they are and providing comprehensive risk factor modification that incorporates social determinants of health. 12 Once risk is relayed, we should consider disruptive approaches to mitigate these disparities in risk. Approaches to consider include embedding interventions in community settings like the barbershop, 13 employing different delivery strategies such as fixed-dose combination drug therapies, 14 and altering policies to support healthier dietary patterns like Dietary Approaches to Stop Hypertension and plant-based diets.…”
Section: Charting the Path Forwardmentioning
confidence: 99%
“…Studies reported either using EHR to identify at-risk patients who may need social and economic assistance, 24 , 31 , 43 or in-person screening—usually including descriptions about responsible care team members and the time frame for SDOH screening. 22 , 25 , 26 , 29–34 , 36 , 38–40 , 44 , 48 , 49 However, the time frame for data entry into the EHR was not discussed in studies. Of all the studies reviewed, only one 41 reported the process of SDOH screening and capturing responses as standard International Classification of Diseases, 10th Revision (ICD-10) codes in the EHR.…”
Section: Resultsmentioning
confidence: 99%